The Immune Checkpoint PD-1 in Natural Killer Cells: Expression, Function and Targeting in Tumour Immunotherapy - Linda Quatrini (Cancers, 2020)
In the last years, immunotherapy with antibodies against programmed cell death protein 1 (PD-1) and programmed death-ligand 1 (PD-L1) has shown remarkable efficacy in the treatment of different types of tumours, representing a true revolution in oncology. While its efficacy has initially been attributed only to unleashing T cell responses, responsivity to PD-1/PD-L1 blockade was observed in some tumours with low Human Leukocyte Antigen (HLA) I expression and increasing evidence has revealed PD-1 surface expression and inhibitory function also in natural killer (NK) cells. Thus, the contribution of anti-PD-1/PD-L1 therapy to the recovery of NK cell anti-tumour response has recently been appreciated. Here, we summarize the studies investigating PD-1 expression and function in NK cells, together with the limitations and perspectives of immunotherapies. A better understanding of checkpoint biology is needed to design next-generation therapeutic strategies and to improve the clinical protocols of current therapies.